Early Treatment for Community Health Services in Chile. Analytical Article - Sandoval Vidal, Hector Paulo; Universidad de La Frontera (Editorial Pontificia Universidad Javeriana, 2014)
Background: Challenges met to implement early orthodontics in community health services contrast with public policies that promote preventive and interceptive child care. Purpose: Introduce a proposal for clinical intervention on children based on an eight-year pilot experience using early orthodontic therapies at the Universidad de la Frontera with patients of fourth and fifth year dental students and clinics in the southern Chilean region. Methods: The proposal analyzes the bases of an adequate diagnosis and subsequent treatment of craneofacial abnormalities frequent among children, as well as the development of the appliances. Results: The proposal includes, first, addressing bad habits among class II patients; second, maxillary protraction for Class III patients; and tooth eruption control in Class I patients. Conclusions: Patients who use their devices with discipline get adequate three-dimensional results. Relationship with the parents and children motivation are key factors in deciding whether to treat a child with coaches, protraction face mask, or dynamic space maintainers. Even though this does not preclude all patients from needing corrective orthodontic treatments, tissue conditions improve for future interventions. Incorporating prefabricated appliances may provide increased coverage, as long as dentists who treat children understand their scope and limitations.KEYWORDSearly treatment; habits; maxillary protraction; tooth eruption; dentofacial anomalies; deciduous dentition